1994
DOI: 10.1136/bmj.308.6943.1531
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of tuberculosis to slim disease in Africa

Abstract: Wasting and chronic diarrhoea are late stage manifestations of HIV disease in Africa. The importance of tuberculosis as a contributing factor in the pathogenesis of the slim syndrome has been underestimated. In nearly half of patients dying with severe wasting, tuberculosis was the dominant pathological finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0
2

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 21 publications
1
66
0
2
Order By: Relevance
“…Is unexplained weight loss a proxy for bacteraemia or undiagnosed TB, both of which could present in an atypical or covert manner? 17 A recent study from northern Malawi showed that 77% of patients who developed TB after starting ART had unexplained weight loss and/or fever before starting ART, and these observations concur with this hypothesis. 18 In any case, this is a group of patients in whom intensified casefinding for TB and other opportunistic infections might be worthwhile.…”
Section: Discussionsupporting
confidence: 77%
“…Is unexplained weight loss a proxy for bacteraemia or undiagnosed TB, both of which could present in an atypical or covert manner? 17 A recent study from northern Malawi showed that 77% of patients who developed TB after starting ART had unexplained weight loss and/or fever before starting ART, and these observations concur with this hypothesis. 18 In any case, this is a group of patients in whom intensified casefinding for TB and other opportunistic infections might be worthwhile.…”
Section: Discussionsupporting
confidence: 77%
“…Few studies (Serwadda et al, 1985;Lucas et al, 1994;Kennedy et al, 1996;Harries et al, 1988) have been dedicated to the prevalence of malnutrition among African adults, although it is a problem increasingly faced by practitioners in places with a high prevalence of HIV infection. These studies consisted of autopsy series of HIV-seropositive subjects (Lucas et al, 1994); or speci®-cally focused on cachectic HIV-seropositive patients (Serwadda et al, 1983) or TB patients (Kennedy et al, 1996;Harries et al, 1988), but none evaluated the burden of malnutrition among patients admitted to internal medicine wards and its signi®cance for medical practice in a city where both HIV infection and TB are common.…”
Section: Introductionmentioning
confidence: 99%
“…These studies consisted of autopsy series of HIV-seropositive subjects (Lucas et al, 1994); or speci®-cally focused on cachectic HIV-seropositive patients (Serwadda et al, 1983) or TB patients (Kennedy et al, 1996;Harries et al, 1988), but none evaluated the burden of malnutrition among patients admitted to internal medicine wards and its signi®cance for medical practice in a city where both HIV infection and TB are common. We therefore carried out a nutritional survey among adult inpatients in Bujumbura in order to evaluate the prevalence and to identify the causes (including HIV infection) of malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…In Co Ãte d'Ivoire, West Africa, 44% of the patients who die during hospitalization suffer wasting syndrome (Lucas et al, 1994). It is de®ned by`an involuntary weight loss of more than 10% of baseline body weight, plus either chronic diarrhea (at least two loose stools per day for 530 d), or chronic weakness and documented fever (for 530 d, intermittent or constant) in the absence of concurrent illness or condition other than HIV infection that could explain the ®ndings' (CDC, 1987).…”
Section: Introductionmentioning
confidence: 99%